Integrative Model of Islamic Religious Education through Habituation and Mutaba’ah at SMK Tiara Lahat - Balkis, Lutfiah Holifa; Achadi , Muh. Wasith (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2026)
This study is motivated by the low level of students’ religious practices in general schools, which are not yet optimal in developing religious character. This study aims to analyze the innovation of the Islamic Religious Education (PAI) curriculum based on religious habituation and mutaba’ah at SMK Tiara Lahat. This research uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving a PAI teacher, the vice principal of curriculum, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the PAI curriculum innovation is implemented through digital-based learning, religious habituation such as prayer, dhikr, Qur’an recitation submission, congregational dhuha and zuhr prayers, and mutaba’ah-based evaluation. This innovation positively impacts students’ religious awareness, both in understanding and in practicing religious values. In conclusion, the innovation of the PAI curriculum based on religious habituation and mutaba’ah can serve as an alternative model for curriculum development in general schools, although improvements in facilities and environmental support are still needed.